Devil's food cake murder [large type] - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2011)
Hannah Swensen has to admit life is pretty sweet. Things are going well in the romance department, and her bakery<U+2019>s delectable confections are selling as fast as she can make them. Even her good friend Claire is head over heels with her new husband, Reverend Bob Knudson. If only they could find time to take their honeymoon! When Bob<U+2019>s childhood friend, Matthew Walters, comes to town, it seems like divine intervention. Matthew, like Bob, is a Lutheran minister with a stubborn sweet tooth. Since he<U+2019>s on sabbatical, Matthew is happy to fill in for Bob while he and Claire take that long-awaited honeymoon. It sounds like the perfect plan<U+2014>until Hannah finds Matthew facedown in a plate of Devil<U+2019>s Food Cake, a single bullet in his head. And the only witness is a bird who squawks “The wages of sin is death.” It will take some sleuthing for Hannah to sift out the killer<U+2026>